Web-Based Intern Admission System At The ATR / BPN Office Of Medan City Using Weighted Product Method - Purba, Rizki Ikhwansyah; Alda, Muhamad (Jurnal Teknologi Informatika dan Komputer, 2025)
This study designs a web-based internship registration and selection system for the Office of the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) of Medan City, located on Jl. STM, Sitirejo II, Medan Amplas. The system was developed using PHP Native and MySQL, and it is designed to be responsive, allowing access via both desktop and mobile devices. The main goal is to replace the konvensional selection process, which still relies on physical documents and often results in file accumulation, delays, and non-objective evaluations.The primary issue addressed in this research is how to build an internship selection system that is automated, efficient, and objective. To achieve this, the Weighted Product (WP) method was implemented as a decision support system. This method calculates the final score of applicants based on weighted values from three main criteria: GPA, academic program, and completeness of the CV.Key features of the system include: online registration forms, document uploads, automated scoring using the WP method, real-time application status tracking, and an admin dashboard to manage participant data and selection results. The system model is illustrated through a Use Case Diagram, Activity Diagram, and Flowmap to demonstrate user interactions and process flow comprehensively.Research Results Based on the WP method applied to 150 applicants, the normalized Vi values were used to rank participants for each internship position. A total of 27 top-ranking participants were selected to fill 9 positions. For example, Samsul Yolanda (Section 1), Nasrullah Tamba (Section 2), and R.M. Simon Winarno (General Sub-Administration). Applicants ranked 2nd and 3rd for each position may be considered as substitutes if quotas allow. These results demonstrate that the selection process is now more objective, transparent, and competency-based.